Comparative analysis between the SPIF and DPIF variants for die-less forming process for an automotive workpiece (2015)
Over time the process of incremental deformationDie-less has been developed in many ways to meet the needs of flexible production with no invest-ment in tooling and low production costs. Two of their configurations are the SPIF (Single point incremental forming) and DPIF (Double point Incremental form-ing) technique. The aim of this study is to compare both techniques with the purpose of exposing their advan-tages and disadvantages in the production of industri-al parts, as well as to inform about Die-less as an alter-native manufacturing process. Experiments with the exhaust pipe cover of a vehicle are performed, the main process parameters are described, and formed work-pieces without evidence of defects are achieved. Signif-icant differences between the two techniques in terms of production times and accuracy to the original model are also detected. Finally, it is suggested when is more convenient to use each of these.